1998
DOI: 10.1038/sj.gt.3300590
|View full text |Cite
|
Sign up to set email alerts
|

β-Galactosidase staining following intracoronary infusion of cationic liposomes in the in vivo rabbit heart is produced by microinfarction rather than effective gene transfer: a cautionary tale

Abstract: The myocardium is a potential target for the expression of conversion at day 3 with associated myocardial damage. exogenous genes to treat inherited and acquired diseases.We hypothesised that the damage was associated with Although adenovirus-mediated gene transfer has resulted macro-aggregates of cationic liposomes-DNA occluding in high-level gene transfer in vivo via direct intramyocardial the microcirculation. When such aggregates were excluded injection and via a percutaneous intra-arterial route, the no X… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 40 publications
1
20
0
Order By: Relevance
“…X-Gal staining for LacZ gene transfer revealed significant and heterogeneously expression throughout both the sham and banded hearts 48-72 hrs following Ad.cmv.LacZ delivery, similar to the level of overexpression illustrated in figure 4. Importantly, there were no "false positives" for endogenous LacZ expression in hearts as a consequence of microinfarctions formed during the intracoronary infusion as previously speculated by Wright et al (Wright et al, 1998).…”
Section: Negative Outcome With Serca1a In Whole Heart Models Of Heartsupporting
confidence: 52%
“…X-Gal staining for LacZ gene transfer revealed significant and heterogeneously expression throughout both the sham and banded hearts 48-72 hrs following Ad.cmv.LacZ delivery, similar to the level of overexpression illustrated in figure 4. Importantly, there were no "false positives" for endogenous LacZ expression in hearts as a consequence of microinfarctions formed during the intracoronary infusion as previously speculated by Wright et al (Wright et al, 1998).…”
Section: Negative Outcome With Serca1a In Whole Heart Models Of Heartsupporting
confidence: 52%
“…Gene Therapy detection of efficient adenoviral gene transfer using both reporter genes argues against false positive ␤-galactosidase staining due to microinfarctions. 20 Furthermore, there was no evidence for microinfarctions in these probes by histological assessment.…”
Section: Comparison Of Passage Timementioning
confidence: 99%
“…8 We previously demonstrated that interpretation of results when using the LacZ reporter is complicated by potential artefacts that may in part explain this discrepancy. 9 by oxygenated perfluorocarbon emulsion as viral diluent Further understanding of the factors involved in gene transfer by intracoronary delivery of recombinant adenovirus has been gained through a series of experiments involving Langendorff perfusion. 10,11 These studies show that the coronary flow rate, absolute amount of virus, time spent in the coronary circulation and composition of perfusate were major factors affecting intracoronary gene transfer 10 and increasing capillary permeability leads to improvements in gene transfer efficiency.…”
Section: Introductionmentioning
confidence: 99%